DESAIN DAN KONSTRUKSI PENYULING AIR ASIN MENJADI AIR TAWAR (SOLAR STILL) YANG MUDAH, MURAH DAN MEMILIKI EFISIENSI TINGGI - Patunrengi1, Iswadi I.; Aisyah, Aisyah; Said L, Muh; FA, Nurul (JFT: Jurnal Fisika dan Terapannya, 2021)
Solar still design and construction have been carried out with two models, namely the pyramid model and the prism model. The prism model is proposed as a new model that is easier and cheaper in the construction process as a potential replacement for the previous model that is more complicated. While the pyramid model is a control model. The size of the container or raw water bath used is 75 cm x 75 cm x 10 cm. the results showed that the volume of water evaporated pyramid model more than the control model, efficiency also gave a better value of 27.55% compared to 24.10% for the control model.